Estimating acoustic cue rates in bowhead whales, Balaena mysticetus, during their fall migration through the Alaskan Beaufort Sea - Blackwell, Susanna B.; Thode, Aaron M.; Conrad, Alexander S.; Ferguson, Megan C.; Berchok, Catherine L.; Stafford, Kathleen M.; Marques, Tiago A.; Kim, Katherine H. (The Journal of the Acoustical Society of America, 2021)
Funding for the ASAMM project is from Bureau of Ocean Energy Management (BOEM) Interagency Agreements M07RG13260 and M11PG00033 (C. Monnett, R. Denton, and C. Fairfield). Funding for the NOAA mooring and analysis is from BOEM: CHAOZ–M09PG00016 (C. Monnett and H. Crowley) and ARCWEST–M12PG00021 (C. Monnett, J. Denton, and H. Crowley). Funding for the UW mooring and analysis is from National Oceanographic Partnership Program (NOPP) Grant No. N00014-08-1-0311 and National Science Foundation (NSF) Grant Nos. ARC-0856244 and ARC-855828 to K.M.S. from the Office of Polar Programs of the NSF. T.A.M.’s time was covered by the Living Marine Resources (LMR) ACCURATE project (Contract No. N3943019C2176) and partial support by the Center of Statistics and its Applications (CEAUL) (funded by FCT–Fundação para a Ciência e a Tecnologia, Portugal, through Project No. UIDB/00006/2020). Eight years of passive acoustic data (2007–2014) from the Beaufort Sea were used to estimate the mean cue rate (calling rate) of individual bowhead whales (Balaena mysticetus) during their fall migration along the North Slope of Alaska. Calls detected on directional acoustic recorders (DASARs) were triangulated to provide estimates of locations at times of call production, which were then translated into call densities (calls/h/km2). Various assumptions were used to convert call density into animal cue rates, including the time for whales to cross the arrays of acoustic recorders, the population size, the fraction of the migration corridor missed by the localizing array system, and the fraction of the seasonal migration missed because recorders were retrieved before the end of the migration. Taking these uncertainties into account in various combinations yielded up to 351 cue rate estimates, which summarize to a median of 1.3 calls/whale/h and an interquartile range of 0.5–5.4 calls/whale/h. Peer reviewed